Komunikasi Pemasaran Digital PT. Adhi Darma Cargo Dalam Upaya Membangun Brand Awareness - Anggreswari, Ni Putu Yunita; Nugraha, I Putu Jaya Putra; Parasari, Nyoman Sri Manik; Maheswari, Anak Agung Istri Agung (representamen, 2025)
Adhi Darma Cargo is a company that operates in the logistics sector, particularly in cargo management. Currently, Adhi Darma Cargo is undergoing a leadership transition, initially led by I Nyoman Mawiana and now shifting to the leadership of his eldest son, Hendra Arimbawa. Under Hendra's leadership, the company is focused on building brand awareness through digital media. This approach acknowledges that the first generation of Adhi Darma Cargo tended to emphasize simpler methods for brand awareness. As the company enters a new era of globalization, it recognizes that information in the digital realm circulates rapidly. This research utilizes integrated marketing communication theory, comprising five elements: advertising, sales promotion, public relations and publicity, direct marketing, and personal selling. According to the research findings, Adhi Darma Cargo has implemented these five elements of the marketing communications mix through its extensive use of digital media, particularly social media. With this implementation of the marketing communications mix, Adhi Darma Cargo aims to achieve high brand awareness and become better recognized by the broader community as one of the top choices for quality cargo services Bali. Keywords: Cargo, Marketing Communication Mix, Brand Awareness